Ammonia decomposition catalyst and exhaust gas treatment method
By using a mixture of the first catalyst powder composed of a carrier and a noble metal and the second catalyst powder obtained by ion exchange as a catalyst, the problems of low decomposition efficiency of ammonia and ammonia oxides and poor catalyst resistance in the prior art are solved, and efficient and harmless treatment of exhaust gas is achieved.
Patent Information
- Application Number
- CN202380060580.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-29
- Filing Date
- 2023-08-25
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to efficiently decompose by-products in ammonia (NH3) and ammonia oxides (NOX and N2O), and the catalyst is prone to deterioration at high temperatures, affecting the harmless treatment of exhaust gas.
A mixture consisting of the first catalyst powder and the second catalyst powder are used as the catalyst. The first catalyst powder contains a carrier and a noble metal. The second catalyst powder is obtained by ion exchange and has excellent high temperature resistance.
The efficient decomposition of ammonia, NOX and N2O is achieved, deterioration caused by SO2 is avoided, and the stability of the catalyst is maintained at a high temperature above 500°C.
Smart Images

Figure BDA0005276199340000231 
Figure BDA0005276199340000261 
Figure BDA0005276199340000291
Abstract
Description
Technical Field
[0001] The present invention relates to a catalyst for promoting ammonia decomposition reaction and a method for rendering a treated gas harmless. More specifically, the present invention relates to a catalyst for promoting ammonia decomposition reaction and a method for rendering a waste gas harmless, wherein the catalyst for promoting ammonia decomposition reaction can efficiently promote a chemical reaction for decomposing ammonia (NH3), and can efficiently promote the oxidation of NO produced as a by-product in the oxidation reaction of NH3. X The present invention relates to a chemical reaction for decomposing N2O and / or N2O, and there is almost no degradation caused by SO2 that may be contained in the combustion exhaust gas, and the catalyst for promoting the decomposition reaction of ammonia has excellent high temperature resistance, and the method for making the exhaust gas harmless can efficiently decompose NH3 contained in the treated gas, and can efficiently decompose NO contained in the treated gas that is a by-product of the oxidation reaction of NH3. X and / or N2O. Background Art
[0002] Carbon dioxide is known as a greenhouse gas. Therefore, research is underway to develop ammonia fuels that do not emit carbon dioxide when burned. When ammonia fuels are burned, they produce NH3, NO X and N2O. This exhaust gas may have adverse effects on the environment. In addition, in the field of storing / using ammonia, such as ammonia fuel ships, ammonia transport ships, ammonia fuel storage bases, ammonia tanks for denitration devices in power plants, ammonia cooling / refrigeration equipment, etc., a large amount of ammonia is released when, for example, tanks or pipes are purged with nitrogen, etc. In the treatment of ammonia-containing wastewater such as food / drinking water manufacturing wastewater, chemical plant wastewater, electroplating wastewater, semiconductor parts manufacturing wastewater, and domestic wastewater, for example, a large amount of ammonia is released in diffusion towers, etc. Ammonia is a malodorous substance that causes mucous membrane irritation, respiratory tract irritation, conjunctival edema, corrosion, etc.
[0003] In order to render a gas containing NH 3 or the like harmless, various catalysts and methods have been proposed.
[0004] For example, Patent Document 1 discloses an ammonia decomposition catalyst for treating ammonia exhaust gas containing water, comprising: a lower layer having a noble metal, an inorganic oxide, and phosphorus, and having a first proton-type zeolite or a first ion-exchange zeolite ion-exchanged with Cu, Co, or Fe ions; and an upper layer, which is disposed on the lower layer and has a second proton-type zeolite or a second ion-exchange zeolite ion-exchanged with Cu, Co, or Fe ions. The ammonia decomposition catalyst specifically disclosed in the embodiment of Patent Document 1 is as follows: a substance obtained by coating a mixture of platinum-loaded titanium dioxide and Cu ion-exchanged β-type zeolite on a carrier, drying and calcining the mixture to obtain a lower layer, coating the mixture with an aqueous phosphoric acid solution, and then coating the mixture with a substance obtained by mixing silica sol and Cu ion-exchanged β-type zeolite to obtain an upper layer.
[0005] Patent document 2 discloses a catalyst, wherein a zeolite loaded with iron is used as the first component, and the noble metal composition pre-loaded on a porous body such as a noble metal salt of platinum or palladium or a zeolite, alumina, or silica is used as the second component, and the catalyst has carbon monoxide decomposition activity, ammonia decomposition activity, nitrous oxide decomposition activity, and nitrogen monoxide decomposition activity. Patent document 2 specifically discloses that mordenite or pentasil type zeolite is used as the first component in the examples.
[0006] Patent document 3 discloses a method for manufacturing a catalytic particulate filter, which includes the following steps: a) providing a porous filter body having a dispersion side and a permeation side; b) providing a catalyst carrier coating, which contains: particles of a first catalyst composition active in the selective catalytic reduction of nitrogen oxides; particles of a second catalyst composition active in the oxidation of carbon monoxide, hydrocarbons and ammonia; and a third catalyst composition active in the selective oxidation of ammonia to nitrogen together with the second catalyst composition, wherein the particles of the first catalyst composition have a mode particle size smaller than the average pore size of the particulate filter, and the second and third catalyst compositions have a mode particle size larger than the average pore size of the particulate filter; c) coating the filter body with the catalyst carrier coating by introducing the carrier coating into the outlet end of the permeation side; and d) drying and heat-treating the coated filter body to obtain a catalytic particulate filter.
[0007] Patent documents 4 and 5 disclose a catalyst comprising: an oxide of titanium (Ti); an oxide of one or more elements selected from tungsten (W), vanadium (V) and molybdenum (Mo); and silica, zeolite and / or alumina supported with one or more precious metals selected from platinum (Pt), iridium (Ir), rhodium (Rh) and palladium (Pd).
[0008] Patent Document 6 discloses a catalyst for removing nitrogen oxides, characterized in that it contains a catalyst component obtained by calcining a precipitate obtained by precipitating an aqueous liquid containing a soluble titanium compound, a soluble tungsten compound, and a soluble cerium compound in an aqueous medium.
[0009] Patent Document 7 discloses a catalyst for removing nitrous oxide in exhaust gas by ammonia reduction, which is characterized in that iron is supported on β-type zeolite.
[0010] Patent document 8 discloses an ammonia oxidation catalyst device, which comprises a substrate, a first catalyst coating layer and a second catalyst coating layer, wherein the first catalyst coating layer comprises inorganic oxide particles and a catalyst noble metal supported on the inorganic oxide particles, and the second catalyst coating layer comprises NO X Selecting a reduction catalyst and a proton zeolite. In the ammonia oxidation catalyst device specifically disclosed in the examples of Patent Document 8, the first catalyst coating layer is formed of alumina carrying platinum, and the second catalyst coating layer is formed of ferrovanadium and BEA type zeolite.
[0011] Patent document 9 discloses an exhaust gas treatment system for a lean burn engine, the exhaust gas treatment system comprising a diesel oxidation catalyst (DOC), a catalytic soot filter (CSF), a first reductant injector, an AEI zeolite-based selective catalytic reduction (SCR) catalyst, and a first ammonia oxidation catalyst (AMO) located downstream of the AEI zeolite-based SCR catalyst. X ), wherein the molar ratio of silica to alumina of the AEI zeolite is 10 to 19, preferably 14 to 18. Previous technical literature Patent Literature
[0012] Patent Document 1: WO2015 / 099024A1 Patent Document 2: Japanese Patent Application Laid-Open No. 9-884 Patent Document 3: Japanese Patent Application Publication No. 2014-508631 Patent Document 4: Japanese Patent Application Publication No. 2004-216300 Patent Document 5: Japanese Patent Application Publication No. 2002-66538 Patent Document 6: Japanese Patent Application Laid-Open No. 8-257402 Patent Document 7: Japanese Patent Application Laid-Open No. 8-57262 Patent Document 8: Japanese Patent Application Publication No. 2020-182898 Patent Document 9: Japanese Patent Application Publication No. 2022-515962 Summary of the invention Technical issues to be solved by the invention
[0013] The present invention aims to provide a catalyst for promoting the decomposition reaction of ammonia and a method for making exhaust gas harmless, wherein the catalyst for promoting the decomposition reaction of ammonia can efficiently promote the chemical reaction of decomposing ammonia (NH3) and can efficiently promote the oxidation of NO produced as a by-product in the oxidation reaction of NH3. X The present invention relates to a chemical reaction for decomposing N2O and / or N2O, and there is almost no degradation caused by SO2 that may be contained in the combustion exhaust gas, and the catalyst for promoting the decomposition reaction of ammonia has excellent high temperature resistance, and the method for making the exhaust gas harmless can efficiently decompose NH3 contained in the treated gas, and can efficiently decompose NO contained in the treated gas that is a by-product of the oxidation reaction of NH3. X and / or N2O. Means for solving technical problems
[0014] [1] A catalyst for promoting a decomposition reaction of ammonia, comprising a mixture of a first catalyst powder and a second catalyst powder. The first catalyst powder includes a support containing at least one selected from the group consisting of ceria, silica, alumina, titania, zirconia and zeolite, and a noble metal supported on the support. The second catalyst powder includes ion-exchange of at least one ion selected from the group consisting of Fe ions, Ce ions, Co ions, and Cu ions with zeolite.
[0015] [2] The catalyst according to [1], wherein The first catalyst powder comprises a support containing silicon dioxide and / or titanium dioxide and platinum and / or iridium supported on the support. The second catalyst powder includes what is obtained by ion-exchanging Fe ions with BEA-type zeolite.
[0016] [3] A catalyst for promoting a decomposition reaction of ammonia, comprising a mixture of a first catalyst powder, a second catalyst powder and a third catalyst powder, The first catalyst powder includes a support containing at least one selected from the group consisting of ceria, silica, alumina, titania, zirconia and zeolite, and a noble metal supported on the support. The second catalyst powder includes a substance obtained by ion-exchanging at least one ion selected from the group consisting of Fe ions, Ce ions, Co ions, and Cu ions with zeolite. The third catalyst powder includes titanium oxide, tungsten and / or molybdenum oxide, and cerium and / or vanadium oxide. [4] The catalyst according to [3], wherein The first catalyst powder comprises a support containing silicon dioxide and / or titanium dioxide and platinum and / or iridium supported on the support. The second catalyst powder includes a substance obtained by ion-exchanging Fe ions with BEA-type zeolite. The third catalyst powder includes titanium oxide, tungsten oxide, and cerium oxide.
[0017] [5] The catalyst according to any one of [1] to [4], wherein The amount of the noble metal contained is 0.05 to 200 ppm. [6] The catalyst according to any one of [1] to [5], wherein The second catalyst powder is contained in an amount of 1 to 100 parts by mass based on 1 part by mass of the first catalyst powder.
[0018] [7] A catalyst body for promoting a decomposition reaction of ammonia, comprising: a carrier; and the catalyst according to any one of [1] to [6] supported on the carrier. [8] A catalyst body for promoting a decomposition reaction of ammonia, which is formed from a molded body containing the catalyst according to any one of [1] to [6].
[0019] [9] A method for rendering a gas to be treated harmless, comprising the steps of: in the presence of a catalyst as described in any one of [1] to [6] or a catalyst as described in any one of [7] to [8], performing a chemical reaction to convert NH3 contained in the gas to nitrogen and water and to convert NO contained in the gas to X The chemical reaction of N2O into nitrogen and water.
[0020]
[10] The method according to [9] further comprises the step of adding at least one reaction aid selected from the group consisting of ammonia and urea to the treated gas.
[11] The method according to
[10] , further comprising: X and N2O to adjust the amount of the reaction aid added to the treated gas.
[0021]
[12] The method according to any one of [9] to
[11] , further comprising the step of cooling the treated gas.
[13] The method according to
[12] further includes a step of adjusting the cooling degree of the treated gas according to the temperature of the treated gas.
[14] The method according to
[12] or
[13] , wherein the gas to be processed is cooled by adding atmospheric air to the gas to be processed. Effects of the Invention
[0022] The catalyst of the present invention can efficiently promote the chemical reaction of decomposing ammonia (NH3), and can efficiently promote the oxidation reaction of NH3 and the by-product NO X The catalyst of the present invention is suitable for chemical reactions for detoxifying exhaust gases containing NH3 and the like. The method of the present invention can efficiently decompose NH3 contained in the treated gas, and can efficiently decompose NO contained in the treated gas which is a by-product of the oxidation reaction of NH3. X The method of the present invention is suitable for rendering waste gas containing NH3 and the like harmless.
[0023] The chemical reaction that can convert NH3 into nitrogen and water (direct decomposition reaction of ammonia) is represented by formula (4). 4NH3+3O2→2N2+6H2O(4) This chemical reaction is accompanied by heat generation. If a large amount of ammonia and oxygen are supplied to the catalyst layer, the chemical reaction may proceed excessively, generating hot spots in the catalyst layer, thereby causing thermal degradation of the catalyst. The catalyst of the present invention promotes the direct decomposition reaction of ammonia. In particular, the catalyst of the present invention described in [3] does not thermally deteriorate even at a high temperature of 500°C or more and promotes the direct decomposition reaction of ammonia.
[0024] Can make NO X The chemical reaction of nitrogen and water (NO X The decomposition reaction of ) is represented by equations (6), (7) and (8). 4NO+4NH3+O2→4N2+6H2O(6) 6NO2+8NH3→7N2+12H2O(7) NO+NO2+2NH3→2N2+3H2O(8) The chemical reaction that can convert N2O into nitrogen and water (N2O decomposition reaction) is represented by equation (9). 3N2O+2NH3→4N2+3H2O(9) The catalyst of the present invention also promotes NO X The decomposition reaction of and the decomposition reaction of N2O.
[0025] The chemical reactions (side reactions) represented by the formula (1), formula (2), and formula (3) may proceed in parallel with the chemical reaction represented by the formula (4). 4NH3+5O2→4NO+6H2O(1) 4NH3+7O2→4NO2+6H2O(2) 2NH3+2O2→N2O+3H2O(3) These NO generated in the side reactions x and N2O are harmful substances that affect the environment. As mentioned above, the catalyst of the present invention also promotes NO X The decomposition reaction of NH3 and the decomposition reaction of N2O, therefore, as a result, the catalyst of the present invention promotes the decomposition reaction of NH3 via the intermediate (NO X and N2O) into nitrogen and water (indirect decomposition reaction of ammonia). BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a graph showing changes in NH 3 concentration at the reactor outlet at 550°C. Figure 2 is the NO at the reactor outlet at 550°C X Graph of concentration changes. Figure 3 It is a graph showing the change in N2O concentration at the reactor outlet at 550°C. Figure 4 It is a graph comparing the NH3 concentration at the reactor outlet at 550°C. Figure 5 The NO at the reactor outlet at 550 °C is compared X Concentration diagram. Figure 6 is a graph comparing the N2O concentration at the reactor outlet at 550°C. Figure 7 This is a graph showing the temperature dependency of the NH 3 decomposition rate. Figure 8 yes Figure 7 An enlarged view of the main part. Fig. 9 Yes means NO X Plot of the temperature dependence of the decomposition rate (denitrification rate). Fig.10 It is a graph showing the temperature dependence of the N2O concentration at the reactor outlet. Fig.11 It is a graph comparing the decomposition rates of NH3. Fig.12 It is a graph comparing the denitrification rates. Fig.13 is a graph comparing the N2O concentration at the reactor outlet. Fig.14 This is a diagram showing an example of an apparatus for detoxifying high-temperature NH 3 -containing gas. Fig.15 This is a diagram showing an example of an apparatus for detoxifying low-temperature NH 3 -containing gas. Fig.16 This is a diagram showing an example of an apparatus for detoxifying high-temperature NH 3 -containing gas. Fig.17 This is a diagram showing an example of an apparatus for detoxifying high-temperature NH 3 -containing gas. Fig.18 This is a diagram showing an example of an apparatus for detoxifying high-temperature NH 3 -containing gas. DETAILED DESCRIPTION
[0027] The catalyst of the present invention is a catalyst for promoting a decomposition reaction of ammonia. The catalyst of the present invention comprises a mixture of a first catalyst powder and a second catalyst powder or a mixture of a first catalyst powder, a second catalyst powder and a third catalyst powder.
[0028] The first catalyst powder includes a support and a noble metal.
[0029] The support is a support containing at least one selected from the group consisting of ceria, silica, alumina, titania, zirconia and zeolite. As the support, a support containing silica and / or titania is preferably used. The support is preferably porous. The specific surface area of the support is not particularly limited, and is preferably 10 to 1,000 m 2 / g, more preferably 100 to 500 m 2 / g. Specific examples of the support include the following: cerium dioxide powder, silicon dioxide powder, aluminum oxide powder, titanium dioxide powder, zirconium oxide powder or zeolite powder; a mixture of two or more powders selected from the group consisting of cerium dioxide powder, silicon dioxide powder, aluminum oxide powder, titanium dioxide powder, zirconium oxide powder or zeolite powder; a powder of a composite of two or more selected from the group consisting of cerium dioxide, silicon dioxide, aluminum oxide, titanium dioxide and zirconium oxide (for example, silicon dioxide titania, aluminum oxide titania, cerium dioxide titania, silicon dioxide alumina, silicon dioxide zirconia, aluminum oxide zirconia, etc.); a powder obtained by doping, supporting or compounding at least one element selected from the group consisting of cerium dioxide powder, silicon dioxide powder, aluminum oxide powder, titanium dioxide powder, zirconium oxide powder and zeolite powder and different from the element constituting the powder and / or other base metal elements such as molybdenum, tungsten and vanadium. Powders obtained by doping, supporting or compounding tend to have high resistance to hydrothermal aging.
[0030] The noble metal is at least one selected from the group consisting of gold, silver, platinum, ruthenium, rhodium, palladium, osmium, iridium and rhenium. As the noble metal, platinum and / or iridium are particularly preferably used.
[0031] In the first catalyst powder, the noble metal is supported on the support. The ratio of the noble metal in the first catalyst powder to the support is preferably 0.01 to 10% by mass, more preferably 0.02 to 5% by mass, and even more preferably 0.05 to 2% by mass.
[0032] In the first catalyst powder, other metal elements other than the precious metal may also be loaded on the carrier. As other metal elements, rare earth elements such as cerium (Ce), base metal elements such as molybdenum, tungsten, and vanadium can be cited. Unless the effect of the present invention is hindered, the ratio of the rare earth elements in the first catalyst powder to the carrier is not particularly limited. For example, the ratio of the mass of the rare earth elements in the first catalyst powder to the mass of the precious metal is preferably greater than 1 and less than 10, more preferably greater than 3 and less than 7, and further preferably greater than 4 and less than 6. The first catalyst powder formed by loading other metal elements other than the precious metal on the carrier tends to have high resistance to hydrothermal aging.
[0033] The preparation of the first catalyst powder includes, for example, the steps of loading the precious metal on a carrier, and then crushing or disintegrating it into powder as needed. The loading can be carried out, for example, by immersing the carrier in a solution, suspension or emulsion containing the precious metal. The loading of other metal elements other than the precious metal can also be carried out in the same manner. After impregnation, kneading, evaporation to dryness, drying and calcination can be carried out. The temperature during drying can be any temperature that can remove the liquid, for example, 100 to 150°C. The temperature during calcination can be any temperature lower than the heat resistance temperature of the carrier, for example, 350 to 550°C. The calcination time is, for example, 1 to 5 hours.
[0034] The first catalyst powder is preferably porous. The pore size distribution of the first catalyst powder is not particularly limited. The first catalyst powder is not particularly limited in particle size distribution as long as it is in a fine powder form. The particle size distribution can be adjusted by pulverization / crushing, classification, etc.
[0035] The second catalyst powder includes zeolite and metal ions capable of ion exchange with the zeolite.
[0036] Examples of the zeolite include amiciite, analcime, barrerite, bellbergite, bikitaite, boggsite, brewsterite, brewsterite-Sr, brewsterite-Ba, chabazite, chabazite-Ca, chabazite-Na, chabazite-K, chabazite-C, chabazite-Na, chabazite-K, chabazite-Sr, chabazite-Ba, chabazite-Ca ...Ba, chabazite-Ca, chabazite-Na, chabazite-K, chabazite-Sr, chabazite-Ba, chabazite-Ba, chabaz hiavennite, clinoptilolite, clinoptilolite-K, clinoptilolite-Na, clinoptilolite-Ca, cowlesite, dachiardite, dachiardite-Ca, dachiardite-Na, edingtonite, epistilbite, erionite, erionite-Na te-Na), erionite-K, erionite-Ca, faujasite, faujasite-Na, faujasite-Ca, faujasite-Mg, ferrierite, ferrierite-Mg, ferrierite-K, ferrierite-Na, garronite, gaultite, gismondite ine), gmelinite, gmelinite-Na, gmelinite-Ca, gmelinite-K, gobbinsite, gonnardite, goosecreekite, gottardiite, harmome, heulandite, heulandite-Ca, heulandite-Sr, heulandite-Na,heulandite-K, hsianghualite, kalborsite, laumontite, levyne, levyne-Ca, levyne-Na, lovdarite, maricopaite, mazzite, merlinoite, mesolite, montesommaite, mordenite, mutinite aite), natrolite, offretite, pahasapaite, partheite, paulingite, paulingite-Na, paulingite-K, paulingite-Ca, perlialite, phillipsite, phillipsite-Na, phillipsite-K, phillipsite-Ca -Ca), pollucite, roggianite, scolecite, stellerite, stilbite, stilbite-Ca, stilbite-Na, terranovaite, thomsonite, tschernichite, tschortnerite, wairakite, weinebeneite, willhenite natural zeolites such as dersonite), yugawaralite, etc.; A-type (LTA-type) zeolite, X-type (FAU-type) zeolite, LSX-type (FAU-type) zeolite, β-type (BEA-type) zeolite, ZSM-5-type (MFI-type) zeolite, ferrierite-type (FER-type) zeolite, mordenite-type (MOR-type) zeolite, L-type (LTL-type) zeolite, Y-type (FAU-type) zeolite, MCM-22-type (MWW-type) zeolite, offretite / erionite-type (O / E-type) zeolite, AEI-type zeolite, AEL-type zeolite, AFT-type zeolite, AFX-type zeolite, CHA-type zeolite, EAB-type zeolite, ERI-type zeolite, KFI-type zeolite, LEV-type zeolite, LTN-type zeolite,Synthetic zeolites such as MSO zeolite, RHO zeolite, SAS zeolite, SAT zeolite, SAV zeolite, SFW zeolite, TON zeolite, and TSC zeolite. Among them, BEA zeolite is preferred. The ratio of SiO2 to Al2O3 in zeolite (SiO2 / Al2O3 ratio) is preferably 5 to 100, more preferably 7 to 50, and further preferably 9 to 30. The higher the proportion of SiO2, the higher the durability of the catalyst, but the higher the proportion of Al2O3, the greater the amount of metal ions that can be ion exchanged, so there is an optimal value for the SiO2 / Al2O3 ratio. Zeolite is preferably porous. The pore size of zeolite is not particularly limited, for example, preferably 0.01 to 10 nm, more preferably 0.2 to 2 nm. ,
[0037] Synthetic zeolite can be obtained, for example, by mixing a silica source, an alumina source, an alkali source, a solvent, an organic structure-directing agent (OSDA), a surfactant, etc. to obtain a starting reaction mixture, and subjecting the mixture to a hydrothermal reaction at high temperature and high pressure in an autoclave. The synthetic zeolite obtained by this method contains an organic component derived from OSDA. However, it seems that the organic component can be removed by subsequent calcination.
[0038] Certain types of synthetic zeolites can be obtained by hydrothermal reaction without using OSDA. Furthermore, certain types of synthetic zeolites can be obtained by mechanochemical treatment and steam synthesis without using OSDA. Synthetic zeolites obtained without using OSDA (hereinafter sometimes referred to as OSDA-free zeolites) do not contain organic components from OSDA. In the present invention, OSDA-free zeolites can be appropriately used. The SiO2 / Al2O3 molar ratio in the OSDA-free zeolite is preferably greater than 1, more preferably greater than 5, and further preferably greater than 8. The upper limit of the SiO2 / Al2O3 molar ratio in the OSDA-free zeolite is, for example, preferably 50, more preferably 45, and further preferably 40.
[0039] As the ion-exchangeable metal ion, at least one ion selected from the group consisting of Fe ion, Ce ion, Co ion and Cu ion is preferred, and Fe ion is more preferred.
[0040] The second catalyst powder is a material in which the cations of the elements constituting the zeolite are exchanged (ion exchanged) with cations of Fe, Ce, Co or Cu. In addition, the second catalyst powder may include a material on which at least one selected from the group consisting of Fe, Ce, Co and Cu is attached (supported) to the zeolite. The ratio of the metal ions capable of ion exchange in the second catalyst powder to the zeolite is preferably 0.1 to 10% by weight, more preferably 0.7 to 7% by weight. The ratio of Fe ions to the zeolite is preferably 0.1 to 10% by weight, more preferably 0.7 to 7% by weight.
[0041] The ion exchange can be performed by immersing the zeolite in a liquid containing metal ions capable of ion exchange, and then filtering / drying / calcining the zeolite as necessary. The pH of the liquid containing the metal ions capable of ion exchange in which the zeolite is impregnated is preferably adjusted. The pH of the liquid containing the metal ions capable of ion exchange is, for example, 1 to 8, preferably 3.5 to 7.5, and more preferably 5.5 to 7.0. In order to adjust the pH, alkaline compounds such as sodium hydroxide, potassium hydroxide, rubidium hydroxide, cesium hydroxide, sodium carbonate, potassium carbonate, or acidic compounds such as hydrochloric acid and nitric acid can be used. The drying temperature may be any temperature at which the liquid can be removed, for example, 100 to 150° C. The calcining temperature may be any temperature lower than the heat resistance temperature of the zeolite, for example, 350 to 800° C. The calcining time may be appropriately set according to the calcining temperature, for example, 1 to 10 hours. After the ion exchange, it may be pulverized or crushed to form a powder as required.
[0042] The second catalyst powder is preferably porous. The pore size distribution of the second catalyst powder is not particularly limited. The second catalyst powder is not particularly limited in particle size distribution as long as it is in a fine powder form. The particle size distribution can be adjusted by pulverization / crushing, classification, etc.
[0043] The second catalyst powder has acidic sites derived from OH groups and the like. The properties of the acidic sites can generally be observed by a method known as the pyridine-TPD method. In the pyridine-TPD method, for example, a hydrogen flame ionization detector (FID) can be used as a detector. Pyridine is adsorbed on the acidic sites. Pyridine can be adsorbed on acidic sites on the outer surface of the pores of the catalyst and on acidic sites on the inner surface of the pores. It is generally believed that the higher the desorption temperature of the adsorbed pyridine, the stronger the acid strength of the acidic sites. In addition, it is also believed that the pyridine desorbed at high temperatures comes from acidic sites affected by diffusion, i.e., acidic sites located on the inner surface of the pores (Nakano et al. "Determination of the Acidic Properties of Zeolites by Temperature Desorption Method" Toyo Soda Research Report Vol. 29 No. 1 (1985), pp3-11). The effective molecular diameter of pyridine is considered to be (Refer to Anderson et al. J. Catal., 58, 114 (1979)). Moreover, the total amount of acid sites can be determined by the saturated adsorption amount of pyridine. When pyridine is adsorbed and then the temperature is raised at a constant rate (20°C / min), the acid strength distribution of the acid sites can be determined by the distribution of the amount of pyridine desorbed at each temperature (this distribution is sometimes referred to as a TPD spectrum). In addition, in the present invention, the adsorption of pyridine can be carried out at room temperature to 150°C, preferably at 150°C.
[0044] In the TPD spectrum of the second catalyst powder, the ratio of the total amount of pyridine desorbed in the range of 150°C to less than 450°C to the total amount of pyridine desorbed in the range of 450°C to 800°C is preferably 0.9 or more, more preferably 0.98 or more, further preferably 1 or more, and further preferably 1.1 or more. As long as production is possible, the upper limit of the ratio of the total amount of pyridine desorbed in the range of 150°C to less than 450°C to the total amount of pyridine desorbed in the range of 450°C to 800°C is not particularly limited.
[0045] In the TPD spectrum of the second catalyst powder, the total amount of pyridine desorbed in the range of 150°C to less than 450°C is preferably 100 μmol or more, more preferably 200 μmol or more, further preferably 250 μmol or more, and further preferably 300 μmol or more relative to 1 g of the catalyst. The upper limit of the total amount of pyridine desorbed in the range of 150°C to less than 450°C is not particularly limited as long as it can be produced.
[0046] In the TPD spectrum of the second catalyst powder, the total amount of pyridine desorbed in the range of 450°C to 800°C is preferably 1000 μmol or less, more preferably 800 μmol or less, and further preferably 500 μmol or less relative to 1 g of the catalyst. The lower limit of the total amount of pyridine desorbed in the range of 450°C to 800°C is not particularly limited as long as it can be produced.
[0047] In the TPD spectrum of the second catalyst powder, the value of the L peak (the amount of pyridine desorbed at the maximum peak top in the range of 150°C or more and less than 450°C) is greater than the value of the H peak (the amount of pyridine desorbed at the maximum peak top in the range of 450°C or more and 800°C or less). That is, the ratio of the value of the L peak to the value of the H peak is preferably greater than 1, more preferably greater than 1.12, further preferably greater than 1.2, further preferably greater than 1.4, and most preferably greater than 1.6. As long as it can be produced, the upper limit of the ratio of the value of the L peak to the value of the H peak is not particularly limited.
[0048] In the TPD spectrum of the second catalyst powder, the lower limit of the temperature at which the H peak appears (the temperature at the maximum peak in the range of above 450°C and below 800°C) is preferably 490°C, more preferably 510°C, and further preferably 530°C, and the upper limit is preferably 650°C, more preferably 620°C, further preferably 600°C, and further preferably 580°C.
[0049] The second catalyst powder is preferably a powder having a large saturated adsorption amount of pyridine. The saturated adsorption amount of pyridine in the second catalyst powder is preferably 100 μmol or more, more preferably 200 μmol or more, further preferably 500 μmol or more, and further preferably 700 μmol or more relative to 1 g of the catalyst. As long as it can be produced, the upper limit of the saturated adsorption amount of pyridine in the second catalyst powder is not particularly limited. For example, it is preferably 2000 μmol, more preferably 1500 μmol relative to 1 g of the catalyst. The saturated adsorption amount of pyridine can be measured at 150°C.
[0050] The second catalyst powder is preferably a powder with a large crystallite size. The crystallite size in the second catalyst powder is preferably 5 nm or more, more preferably 10 nm or more, further preferably 20 nm or more, and further preferably 30 nm or more. As long as it can be manufactured, the upper limit of the crystallite size of the second catalyst powder is not particularly limited, for example, preferably 100 nm, more preferably 80 nm. The crystallite size can be measured by X-ray diffraction (for example, with reference to JIS H 7805 or JIS R 7651).
[0051] The second catalyst powder preferably has a high NO2 decomposition rate and a high NO decomposition rate even after being exposed to a 530°C gas containing 20% H2O and 20ppm SO2 for 70 hours. The second catalyst powder preferably has a NO2 decomposition rate of 60% or more and a NO decomposition rate of 90% or more at 450°C after being exposed to a 530°C gas containing 20% H2O and 20ppm SO2 for 70 hours.
[0052] The third catalyst powder contains titanium oxide, tungsten and / or molybdenum oxide, and cerium and / or vanadium oxide, and preferably contains titanium oxide, tungsten oxide, and cerium oxide.
[0053] The ratio of Ce element and / or V element to Ti element is preferably 1 to 20 wt %, more preferably 3 to 15 wt %, in terms of weight percentage of (CeO 2 + V 2 O 5 ) / TiO 2 . The ratio of the Mo element and / or the W element to the Ti element is preferably 1 to 50% by weight, more preferably 10 to 40% by weight, in terms of the weight percentage of (MoO3+WO3) / TiO2.
[0054] In the preparation of the third catalyst powder, as a raw material for titanium oxide, titanium oxide powder or a titanium oxide precursor can be used. As a titanium oxide precursor, titanium oxide slurry, titanium oxide sol, titanium sulfate, titanium tetrachloride, titanate, titanium alkoxide, etc. can be cited. In the present invention, as a raw material for titanium oxide, anatase-type titanium oxide is preferably used. As a raw material for vanadium oxide, vanadium compounds such as vanadium pentoxide, ammonium metavanadate, and vanadium sulfate can be used. As a raw material for tungsten oxide, ammonium paratungstate, ammonium metatungstate, tungsten trioxide, tungsten chloride, etc. can be used. As a raw material for molybdenum oxide, ammonium molybdate, molybdenum trioxide, etc. can be used. As a raw material for cerium oxide, cerous nitrate, cerous nitrate, cerous carbonate, cerous sulfate, cerous sulfate, cerous acetate, etc. can be used.
[0055] The third catalyst powder may contain P oxide, S oxide, Al oxide (e.g., alumina), Si oxide (e.g., glass fiber), Zr oxide (e.g., zirconium oxide), gypsum (e.g., dihydrate gypsum), zeolite, etc. as promoters or additives. These can be used in the form of powder, sol, slurry, fiber, etc. when preparing the catalyst.
[0056] The preparation of the third catalyst powder includes, for example, adding a solvent (e.g., water) to the raw materials of each oxide and the co-catalyst or additive as required, kneading, evaporating the obtained kneaded product to dryness, drying, calcining, and then crushing or disintegrating it as required to make it into a powder. The temperature during drying can be any temperature at which the liquid can be removed, for example, 100 to 150° C. The temperature during calcination can be any temperature lower than the heat resistance temperature of the oxide, for example, 350 to 550° C. The calcination time is, for example, 1 to 5 hours.
[0057] The third catalyst powder is preferably porous. The pore size distribution of the third catalyst powder is not particularly limited. The third catalyst powder is not particularly limited in particle size distribution as long as it is in a fine powder form. The particle size distribution can be adjusted by pulverization / crushing, classification, etc.
[0058] The catalyst of the present invention can be obtained by mixing a first catalyst powder and a second catalyst powder or by mixing a first catalyst powder, a second catalyst powder and a third catalyst powder. The mixing can be dry mixing or wet mixing. After mixing, drying or calcining, crushing / disintegration, granulation and classification can be performed as needed. The temperature during drying can be any temperature at which the liquid can be removed, for example, 100 to 150°C. The temperature during calcination can be any temperature lower than the heat resistance temperature of the oxide, for example, preferably 350 to 650°C, more preferably 450 to 600°C, and further preferably 480 to 570°C. The calcination time can be appropriately set according to the temperature during calcination, for example, 1 to 5 hours. The catalyst of the present invention is not particularly limited by particle size distribution. The particle size distribution can be adjusted by crushing / disintegration, granulation, classification, etc.
[0059] The mixing ratio of the first catalyst powder to the second catalyst powder or the mixing ratio of the first catalyst powder, the second catalyst powder and the third catalyst powder can be set, for example, to the concentration of NH3, NO X The concentration and N2O concentration were within the specified range.
[0060] The amount of the first catalyst powder contained in the catalyst of the present invention is preferably 0.01 to 10% by mass, more preferably 0.1 to 5% by mass, and even more preferably 0.5 to 3% by mass. The amount of the noble metal contained in the catalyst of the present invention is preferably 0.05 to 1000 ppm, more preferably 0.1 to 500 ppm, and even more preferably 5 to 200 ppm. The second catalyst powder is preferably 1 to 100 parts by mass, more preferably 10 to 70 parts by mass, and even more preferably 20 to 55 parts by mass, relative to 1 part by mass of the first catalyst powder.
[0061] When heat resistance is required, a third catalyst powder can be mixed. The third catalyst powder is preferably 0 to 70 parts by mass, more preferably 0 to 50 parts by mass, and further preferably 0 to 30 parts by mass relative to 1 part by mass of the first catalyst powder. As the proportion of the third catalyst powder increases, the NH3 outlet concentration can be reduced in the reaction at a high temperature of 500°C or more.
[0062] The catalyst of the present invention can be made into a catalyst body by attaching (carrying) the mixture on a carrier, or can be made into a catalyst body by molding the mixture. As the carrier, a plate-like carrier (lath) such as a honeycomb carrier, a corrugated carrier, an expanded metal, a perforated metal (punching metal) etc. can be cited. The amount of the catalyst attached to the carrier can be appropriately set in consideration of the increase in the catalyst filling rate etc. Taking into account the improvement of catalyst filling rate, the suppression of pressure loss increase, etc., the mixture can be formed into shapes such as honeycomb, corrugation, cone, truncated cone, ellipsoid, cone, spindle, Raschig ring, Dixson, saddle, McMahon, etc. After being supported on a carrier or formed, it can be dried or calcined as needed. The temperature during drying can be any temperature at which the liquid can be removed, for example, 100 to 150°C. The temperature during calcination can be any temperature lower than the heat resistance temperature of the oxide, for example, preferably 350 to 650°C, more preferably 450 to 600°C, and further preferably 480 to 570°C. The calcination time can be appropriately set according to the temperature during calcination, for example, 1 to 5 hours.
[0063] The method of the present invention is a method for rendering the treated gas harmless. Here, the treated gas refers to the gas flowing into the catalyst layer (the part where the catalyst of the present invention exists) or the gas passing through the catalyst layer. When the catalyst layers are connected in series in multiple stages, the treated gas includes not only the gas flowing into the previous catalyst layer or the gas passing through the previous catalyst layer, but also the gas flowing into the next catalyst layer or the gas passing through the next catalyst layer.
[0064] The processed gas is a gas containing NH 3 and O 2. For example, when the O 2 concentration of the NH 3 containing gas is high, the NH 3 containing gas can be used directly as the processed gas, and conversely, a gas obtained by mixing the NH 3 containing gas and the O 2 containing gas can be used as the processed gas. As NH3-containing gas, for example, exhaust gas generated by the combustion of ammonia fuel, exhaust gas released during the purging of ammonia-related equipment, or exhaust gas released during the treatment of ammonia-containing wastewater, etc. can be cited. As NH3-containing gas, for example, it is possible to use gas discharged from ammonia fuel ships, ammonia transport ships, ammonia fuel storage bases, ammonia tanks for denitration devices in power plants, ammonia cooling / refrigeration equipment, and other fields where ammonia-containing wastewater such as food / drinking water manufacturing wastewater, chemical plant wastewater, electroplating wastewater, semiconductor parts manufacturing wastewater, and domestic wastewater are treated. When NH3 is dissolved in a liquid, when NH3 is adsorbed on a solid, etc., it is possible to use a substance that has been gasified by a diffusion tower, a vaporizer, etc. As the O2-containing gas, for example, the atmosphere can be used. For example, the mass ratio of O2 to NH3 and the temperature of the treated gas can be set to, for example, the NH3 concentration in the gas flowing out of the catalyst layer or the reactor, the NO XThe concentration of NO and the concentration of N2O are within the specified ranges. Temperature regulation can be performed by known methods, for example, a temperature regulation device such as a heater, a heat exchanger, or a cooler can be used. As a heat transfer medium for regulating the temperature of the treated gas, the gas flowing out of the catalyst layer can be used. The exhaust gas generated by the combustion of ammonia fuel contains NO X and / or N2O. The treated gas may also contain NO X and / or N2O.
[0065] The method of the present invention comprises the following steps: in the presence of the catalyst of the present invention, a chemical reaction is carried out to convert NH3 contained in the treated gas into nitrogen and water and to convert NO contained in the treated gas into X The chemical reaction of NO and N2O into nitrogen and water. X And N2O may be originally contained in the gas flowing into the catalyst layer, or may be generated while passing through the catalyst layer.
[0066] The chemical reaction is preferably carried out in a continuous flow reactor. A catalyst layer is present in the reactor. The continuous flow reactor is a reactor in which a gas adjusted to a predetermined temperature flows in from the reactor inlet, a chemical reaction occurs in the catalyst layer in the reactor, and the gas flows out from the reactor outlet. The catalyst of the present invention can be arranged in the reactor in the form of a fixed bed, a fluidized bed, a moving bed, a simulated moving bed, etc., preferably in the form of a fixed bed or a simulated moving bed. The space velocity of the gas flowing in the reactor [1 / hr] (= volume flow rate (m 3 / hr) / catalyst volume (m 3 )) can be set, for example, to the concentration of NH3, NO X The concentration and the N2O concentration are within the prescribed ranges. The gas temperature at the reactor inlet is preferably 300 to 600°C, more preferably 350 to 550°C, for example.
[0067] The method of the present invention preferably includes the step of adding at least one reaction aid selected from the group consisting of ammonia and urea to the treated gas. In addition, urea is decomposed into carbon dioxide and ammonia by an endothermic reaction. The addition of the reaction aid is preferably carried out at a temperature of 100 °C above the NO X It is carried out when the amount of N2O is large.
[0068] The method of the present invention preferably also includes a step of cooling the treated gas. The gas discharged from a combustion device such as a furnace or an internal combustion engine is usually at a high temperature. The inflow of the high-temperature treated gas causes the temperature of the catalyst layer to rise. Excessive temperature rise of the catalyst layer increases the risk of catalyst degradation. When the temperature of the treated gas is too high, in order to prevent catalyst degradation, it is preferred to cool the treated gas. The cooling of the treated gas can be carried out by adding a low-temperature gas such as the atmosphere to the treated gas, heat exchange between the treated gas and a refrigerant, etc.
[0069] The method of the present invention preferably further comprises the step of: X and the amount of N2O to adjust the amount of the reaction aid added to the treated gas. In addition, the method of the present invention preferably also includes a step of adjusting the degree of cooling of the treated gas according to the temperature of the treated gas. In addition, the temperature of the treated gas is a substitute for the temperature of the catalyst layer. The temperature of the treated gas is preferably measured near the outlet of the catalyst layer and near the outlet of the reactor. When the temperature of the catalyst layer can be directly measured, the temperature can be used. Here, the treated gas refers to the gas flowing out from the catalyst layer (the part where the catalyst of the present invention exists). When the catalyst layer is connected in series into multiple stages, the treated gas includes not only the gas flowing out from the front catalyst layer, but also the gas flowing out from the rear catalyst layer. However, when adjusting the amount of the reaction aid or adjusting the degree of cooling, the treated gas to which the reaction aid is added or cooled is preferably a treated gas located at a more front stage than the treated gas whose temperature has been measured.
[0070] The amount of the reaction aid added and the degree of cooling of the gas to be treated can be adjusted by considering the following points, for example. The direct decomposition reaction of ammonia is an exothermic reaction. If the amount of ammonia used for the direct decomposition reaction increases, the temperature of the catalyst layer increases, and the temperature of the treated gas increases. That is, the addition of a reaction aid sometimes increases the temperature of the treated gas. Furthermore, the inflow of high-temperature treated gas increases the temperature of the catalyst layer. As the temperature of the catalyst layer increases, the speed of the direct decomposition reaction of ammonia and the decomposition reaction of N2O tends to increase. However, the higher the temperature of the catalyst layer, the higher the risk of catalyst degradation. The direct decomposition reaction of ammonia, NO x The decomposition reaction of N2O and the decomposition reaction of N2O will reduce the ammonia in the treated gas. If the ammonia is reduced, it will be difficult to carry out NO x The decomposition reaction of and N2O, NO in the treated gas x Or the amount of N2O may increase.
[0071] The temperature of the gas after each stage of treatment is, for example, preferably 400 to 600° C., more preferably 450 to 550° C. The NO in the gas after the final stage of treatment isX The concentration of N2O is, for example, preferably 500 ppm or less, and more preferably 200 ppm or less. The concentration of N2O in the gas after the final stage of treatment is, for example, preferably 100 ppm or less, and more preferably 10 ppm or less.
[0072] Fig.14 The device for rendering a treated gas harmless includes a reactor 11 and a catalyst layer 12 . Fig.14 The device shown can be applied to the treatment of high temperature NH 3 -containing gas such as NH 3 fuel combustion exhaust gas.
[0073] Fig.15 The device for rendering a treated gas harmless includes a temperature control mechanism, a reactor 11 , a catalyst layer 12 , and a control device 17 . Fig.15 The temperature control mechanism in the device shown is configured to raise the temperature of the gas to be processed to a predetermined temperature. Fig.15 In the device shown, a heat exchanger 9 and a heater 10h are provided. The heater 10h is configured to exchange heat between the treated gas and the treated gas, and the heater 10h is configured to exchange heat between the treated gas and an external heat source. Fig.15 The device shown can be applied to the treatment of low-temperature NH3-containing gas such as purge gas for NH3-related equipment. The structure is such that the treated gas can be obtained by mixing NH3-containing gas A and O2-containing gas B in the mixer 5. The supply amount of NH3-containing gas A and O2-containing gas B can be adjusted by the opening of each control valve. The supply amount of the treated gas supplied to the heat exchanger 9 can be adjusted by the opening of the control valve provided in the heat exchanger bypass pipe 3, thereby adjusting the heat exchanged in the heat exchanger 9. When the temperature of the treated gas can be adjusted, it is not necessary to provide the heat exchanger 9 and / or the heater 10h. The catalyst layer 12 is formed of the catalyst or catalyst body of the present invention and is fixed in the reactor 11. The inflow rate of the treated gas flowing into the catalyst layer can also be adjusted by the opening of the control valve provided in the catalyst layer inflow pipe 2. In order to stably carry out the chemical reaction in the catalyst layer 12, the amount of the treated gas flowing in through the catalyst layer inflow pipe 2 is preferably substantially constant.
[0074] The measuring mechanism measures the physical property values required to monitor the working status of the device. Fig.15 In the device shown, a plurality of measuring instruments 14 are used to measure the gas temperature of the mixer, the gas temperature at the inlet side of the catalyst layer, the NH3 concentration, the O2 concentration, the NO X concentration, N2O concentration, etc.; gas temperature at the outlet of the catalyst layer, NH3 concentration, O2 concentration, NOX concentration, N2O concentration, etc. The control device 17 is configured to control the supply amount of the NH3-containing gas A, the supply amount of the O2-containing gas B, the amount of the treated gas flowing into the catalyst layer, the temperature of the treated gas flowing into the catalyst layer, etc., based on the measured value of the measuring mechanism. The control target of the control device 17 is, for example, to reduce the N2O and NO contained in the exhaust gas 13 without generating a high temperature state such as a hot spot in the catalyst layer. X and / or NH3.
[0075] Fig.16 The device for rendering a treated gas harmless includes a reactor 11 , a catalyst layer 12 , and a control device 17 . Fig.16 The device shown can be applied to the treatment of high-temperature NH3-containing gases such as NH3 fuel combustion exhaust gas. The supply amount of the reaction aid C can be adjusted by the opening of the control valve. The measuring mechanism measures the physical property values required for monitoring the working state of the device. Fig.16 In the device shown, a plurality of measuring instruments 14 are used to measure the gas temperature of the mixer, the gas temperature at the inlet side of the catalyst layer, the NH3 concentration, the O2 concentration, the NO X concentration, N2O concentration, etc.; gas temperature at the outlet of the catalyst layer, NH3 concentration, O2 concentration, NO X concentration, N2O concentration, etc. The control target of the control device 17 is, for example, to reduce N2O and NO contained in the exhaust gas 13 without generating a hot spot or other high temperature state in the catalyst layer. X and / or NH3. In addition, its structure is similar to Fig.14 The devices shown are identical.
[0076] Fig.17 The device for rendering a treated gas harmless includes a temperature control mechanism, a reactor 11 , a catalyst layer 12 , and a control device 17 . Fig.17 The temperature control mechanism in the device shown is configured to lower the temperature of the gas to be processed to a predetermined temperature. Fig.17 In the device shown, a cooling air supply device is provided for lowering the temperature of the gas to be processed. Fig.17 The device shown can be applied to the treatment of high-temperature NH3-containing gas such as exhaust gas from a combustion device. The supply of atmosphere having a lower temperature than the treated gas has the effect of lowering the temperature of the treated gas. Even if a cooler configured to exchange heat with an external cold or heat source is provided, the same effect as the supply of cooling air can be obtained. In addition, its structure is similar to Fig.14 The devices shown are identical.
[0077] Fig.18 The device for rendering a treated gas harmless includes a temperature control mechanism, a reactor 11 , catalyst layers 12 a and 12 b , and a control device 17 . Fig.18 The temperature control mechanism in the device shown is configured to reduce the temperature of the gas flowing out of the catalyst layer 12a to a predetermined temperature before flowing into the catalyst layer 12b. Fig.18 The device shown is provided with a cooler configured to supply cooling air for lowering the temperature of the gas flowing out of the catalyst layer 12a. Fig.18 The device shown can be applied to the treatment of high-temperature NH3-containing gas such as exhaust gas from a combustion device. Even if a cooler configured to exchange heat with an external cold or heat source is provided, the same effect as the supply of cooling air can be obtained. Fig.14 The devices shown are identical.
[0078] Next, examples for demonstrating the effects of the present invention are described, but the scope of the present invention is not limited to these examples.
[0079] [Example 1: Honeycomb catalyst body A] (Preparation of First Catalyst Powder (1)) 100 g of amorphous silica powder was added to an aqueous solution of chloroplatinic acid hexahydrate (H2PtCl6·6H2O) and stirred, and then evaporated to dryness on a sand bath. The dried product was calcined at 500°C in air for 2 hours. The calcined product was crushed to obtain a first catalyst powder (1) in which 0.05% by mass of platinum was supported on the amorphous silica powder.
[0080] (Preparation of Second Catalyst Powder (1)) 60 g of BEA type zeolite powder (SiO2 / Al2O3 ratio = 25) was put into 2000 ml of an aqueous solution containing 9.1 g of iron (II) sulfate heptahydrate (FeSO4·7H2O) heated to 80°C, and then stirred for 2 hours at 80°C to obtain a slurry. The slurry was dehydrated using a suction funnel equipped with filter paper (No.5C). Pure water was injected into the filter cake on the filter paper to wash it. The washed filter cake was dried at 110°C for 12 hours. The dried filter cake was placed in a furnace, heated at 100°C / h, and calcined at 500°C for 5 hours. The calcined product was crushed to obtain a second catalyst powder (1) obtained by ion exchange of Fe ions with zeolite.
[0081] (Preparation of the Third Catalyst Powder) 110 g of cerium (III) nitrate hexahydrate (Ce(NO3)3·6H2O), 385 g of ammonium metatungstate and 55 g of oxalic acid were dissolved in 700 g of water. The aqueous solution was injected into a 300 m2 2 / g or more anatase titanium oxide 715g and specific surface area 90m 2 / g or less anatase-type titanium oxide 385g mixed powder, and kneaded for more than 1 hour. The obtained kneaded product was granulated. The granulated product was dried at 120°C for 4 hours. The dried product was calcined in air at 500°C for 2 hours. The obtained calcined product was crushed to obtain a third catalyst powder containing titanium oxide, tungsten oxide and cerium oxide.
[0082] (Manufacturing of Catalyst Body) 2 parts by mass of the first catalyst powder (1), 78 parts by mass of the second catalyst powder (1), and 20 parts by mass of the third catalyst powder were added to pure water to obtain a slurry. 2 The coating amount was coated on a honeycomb substrate (the honeycomb substrate had an outer diameter that was in contact with the inner surface of the tube wall of the tubular reactor and the outer surface of the honeycomb catalyst body.) It was dried at 120°C for 2 hours. Then, it was calcined at 500°C for 2 hours to obtain a honeycomb catalyst body A. The amount of platinum contained in the catalyst of the honeycomb catalyst body A was 10 ppm.
[0083] (Evaluation of Catalyst (1)) The honeycomb catalyst body A was embedded and fixed in the tubular reactor. The simulated gas A containing the components shown in Table 1 flowed into the tubular reactor at AV=13Nm / hr (AV=gas volume / geometric surface area of the honeycomb catalyst body), and the temperature of the tubular reactor was set to 550°C. The NH3 concentration and NO X The results are shown in Figures 1 to 6 middle.
[0084] [Table 1] Table 1
[0085] [Example 2: Honeycomb catalyst body B] The honeycomb catalyst body B was obtained in the same manner as in Example 1 except that 2 parts by mass of the first catalyst powder (1), 78 parts by mass of the second catalyst powder (1) and 20 parts by mass of the third catalyst powder were changed to 2 parts by mass of the first catalyst powder (1), 88 parts by mass of the second catalyst powder (1) and 10 parts by mass of the third catalyst powder. The honeycomb catalyst body A was changed to the honeycomb catalyst body B. The NH3 concentration and NO concentration at the reactor outlet were measured in the same manner as in Example 1. X The results are shown in Figures 1 to 6 middle.
[0086] [Example 3: Honeycomb catalyst body C] The honeycomb catalyst body C was obtained in the same manner as in Example 1 except that 2 parts by mass of the first catalyst powder (1), 78 parts by mass of the second catalyst powder (1) and 20 parts by mass of the third catalyst powder were changed to 2 parts by mass of the first catalyst powder (1) and 98 parts by mass of the second catalyst powder (1). The honeycomb catalyst body A was changed to the honeycomb catalyst body C. The NH3 concentration and NO concentration at the reactor outlet were measured in the same manner as in Example 1. X The results are shown in Figures 1 to 6 middle.
[0087] [Example 4: Honeycomb catalyst body D] A honeycomb catalyst body D was obtained in the same manner as in Example 1 except that 2 parts by mass of the first catalyst powder (1), 78 parts by mass of the second catalyst powder (1) and 20 parts by mass of the third catalyst powder were changed to 2 parts by mass of the first catalyst powder (1), 70 parts by mass of the second catalyst powder (1) and 28 parts by mass of the third catalyst powder. A honeycomb catalyst body A was changed to a honeycomb catalyst body D. In addition, the NH3 concentration and NO concentration at the reactor outlet were measured in the same manner as in Example 1. X The results are shown in Figures 1 to 6 middle.
[0088] [Example 5: Honeycomb catalyst body E] The honeycomb catalyst body E was obtained in the same manner as in Example 1 except that 2 parts by mass of the first catalyst powder (1), 78 parts by mass of the second catalyst powder (1) and 20 parts by mass of the third catalyst powder were changed to 2 parts by mass of the first catalyst powder (1), 50 parts by mass of the second catalyst powder (1) and 48 parts by mass of the third catalyst powder. The honeycomb catalyst body A was changed to the honeycomb catalyst body E. The NH3 concentration and NO concentration at the reactor outlet were measured in the same manner as in Example 1. X The results are shown in Figures 1 to 6 middle.
[0089] [Example 6: Honeycomb catalyst body F] The honeycomb catalyst body F was obtained in the same manner as in Example 1 except that 2 parts by mass of the first catalyst powder (1), 78 parts by mass of the second catalyst powder (1) and 20 parts by mass of the third catalyst powder were changed to 2 parts by mass of the first catalyst powder (1), 30 parts by mass of the second catalyst powder (1) and 68 parts by mass of the third catalyst powder. The honeycomb catalyst body A was changed to the honeycomb catalyst body F. The NH3 concentration and NO concentration at the reactor outlet were measured in the same manner as in Example 1. X The results are shown in Figures 1 to 6 middle.
[0090] [Example 7: Honeycomb catalyst body G] The honeycomb catalyst body G was obtained in the same manner as in Example 1 except that 2 parts by mass of the first catalyst powder (1), 78 parts by mass of the second catalyst powder (1) and 20 parts by mass of the third catalyst powder were changed to 2 parts by mass of the first catalyst powder (1) and 98 parts by mass of the third catalyst powder. The honeycomb catalyst body A was changed to the honeycomb catalyst body G. The NH3 concentration and NO concentration at the reactor outlet were measured in the same manner as in Example 1. X The results are shown in Figures 1 to 6 middle.
[0091] As described above, the honeycomb catalyst body using the catalyst of the present invention can efficiently (about 97% or more) decompose NH3 even at a high temperature above 500°C. In particular, the honeycomb catalyst bodies A, B, C and D can efficiently decompose NH3 and NO X and removal of N2O.
[0092] [Example 8: Honeycomb catalyst body C] (Manufacturing of Catalyst Body) 2 parts by mass of the first catalyst powder (1) and 98 parts by mass of the second catalyst powder (1) were added to pure water to obtain a slurry. The slurry was mixed at a temperature of 140 g / m 2 The honeycomb substrate was coated with a coating amount of . It was dried at 120° C. for 2 hours. Then, it was calcined at 500° C. for 2 hours to obtain a honeycomb catalyst body C. The amount of platinum contained in the catalyst of the honeycomb catalyst body C was 10 ppm.
[0093] (Evaluation of Catalyst (2)) The honeycomb catalyst body C was fixed in a tubular reactor. The simulated gas B containing the components shown in Table 2 flowed into the tubular reactor at AV=13Nm / hr (AV=gas volume / geometric surface area of the honeycomb catalyst body), and the temperature of the tubular reactor was set to 350℃, 400℃ or 450℃. At each set temperature, the concentrations of NH3 and NO at the reactor outlet were measured. X The decomposition rate of NH3, NO X The results are shown in Figure 7 to Figure 13 middle.
[0094] [Table 2] Table 2
[0095] [Example 9: Honeycomb catalyst body H] The honeycomb catalyst body H was obtained in the same manner as in Example 8 except that 2 parts by mass of the first catalyst powder (1) and 98 parts by mass of the second catalyst powder (1) were changed to 4 parts by mass of the first catalyst powder (1) and 96 parts by mass of the second catalyst powder (1). The amount of platinum contained in the catalyst of the honeycomb catalyst body H was 20 ppm. The honeycomb catalyst body C was changed to the honeycomb catalyst body H. The NH3 concentration and NO concentration at the reactor outlet were measured in the same manner as in Example 8. X The decomposition rate of NH3, NO X The results are shown in Figure 7 to Figure 13 middle.
[0096] [Example 10: Honeycomb Catalyst Body I] (NO X Preparation of reduced catalyst powder The specific surface area is 300m 2 715g of anatase-type titanium oxide powder with a specific surface area of 90m 2 385 g of anatase-type titanium oxide powder with a weight of less than 100 g / g, 194 g of ammonium metatungstate, 80 g of ammonium metavanadate, 103 g of oxalic acid and 560 g of water were mixed to prepare a paste. The obtained paste was granulated. The granulated material was dried at 120°C for 4 hours and then calcined at 500°C for 2 hours. The calcined material was crushed to obtain NO x Reduction catalyst powder.
[0097] 2 parts by mass of the first catalyst powder (1) and 98 parts by mass of the second catalyst powder (1) were changed to 1 part by mass of the first catalyst powder (1) and 99 parts by mass of NO XThe catalyst powder was reduced, and the honeycomb catalyst body I was obtained in the same manner as in Example 8. The amount of platinum contained in the catalyst of the honeycomb catalyst body I was 5 ppm. The honeycomb catalyst body C was changed to the honeycomb catalyst body I, and the NH3 concentration and NO concentration at the reactor outlet were measured in the same manner as in Example 8. X The decomposition rate of NH3, NO X The results are shown in Figure 7 to Figure 13 middle.
[0098] [Example 11: Honeycomb catalyst body J] 2 parts by mass of the first catalyst powder (1) and 98 parts by mass of the second catalyst powder (1) were changed to 4 parts by mass of the first catalyst powder (1) and 96 parts by mass of NO X The catalyst powder was reduced, and the honeycomb catalyst body J was obtained in the same manner as in Example 8. The amount of platinum contained in the catalyst of the honeycomb catalyst body J was 20 ppm. The honeycomb catalyst body C was changed to the honeycomb catalyst body J, and the NH3 concentration and NO concentration at the reactor outlet were measured in the same manner as in Example 8. X The decomposition rate of NH3, NO X The results are shown in Figure 7 to Figure 13 middle.
[0099] [Example 12: Honeycomb catalyst body K] The honeycomb catalyst body K was obtained in the same manner as in Example 8 except that the BEA type zeolite powder was changed to the MOR (mordenite) type zeolite powder (SiO2 / Al2O3 ratio = 25). The honeycomb catalyst body C was changed to the honeycomb catalyst body K. The NH3 concentration and NO concentration at the reactor outlet were measured in the same manner as in Example 8. X The decomposition rate of NH3, NO X The results are shown in Figure 7 to Figure 13 middle.
[0100] [Example 13: Honeycomb catalyst body L] The honeycomb catalyst body L was obtained in the same manner as in Example 8 except that the BEA type zeolite powder was changed to the MFI (pentasilicon) type zeolite powder (SiO2 / Al2O3 ratio = 30). The honeycomb catalyst body C was changed to the honeycomb catalyst body L. The NH3 concentration and NO concentration at the reactor outlet were measured in the same manner as in Example 8. X concentration and N2O concentration, and calculated the NH3 decomposition rate, NO X Decomposition rate (denitrification rate): The result of honeycomb catalyst body L is the same as that of honeycomb catalyst body K.
[0101] [Example 14: Honeycomb catalyst body M] (Preparation of N2O Decomposition Catalyst Powder) 60 g of BEA type zeolite powder (SiO2 / Al2O3 ratio = 25) was put into 2000 ml of an aqueous solution containing 7.3 g of copper (II) sulfate pentahydrate (CuSO4·5H2O) heated to 80°C, and then stirred for 2 hours at 80°C to obtain a slurry. The slurry was dehydrated using a suction funnel equipped with filter paper (No.5C). Pure water was injected into the filter cake on the filter paper to wash it. The washed filter cake was dried at 110°C for 12 hours. The dried filter cake was placed in a furnace, heated at 100°C / h, and calcined at 500°C for 5 hours. The calcined product was crushed to obtain a N2O decomposition catalyst powder obtained by ion exchange of Cu ions with zeolite.
[0102] The honeycomb catalyst body M was obtained in the same manner as in Example 8 except that 2 parts by mass of the first catalyst powder (1) and 98 parts by mass of the second catalyst powder (1) were changed to 2 parts by mass of the first catalyst powder (1) and 98 parts by mass of the N2O decomposition catalyst powder. The honeycomb catalyst body C was changed to the honeycomb catalyst body M. The NH3 concentration and NO concentration at the reactor outlet were measured in the same manner as in Example 8. X concentration and N2O concentration, and calculated the NH3 decomposition rate, NO X Decomposition rate (denitrification rate). The results of honeycomb catalyst body M are the same as those of honeycomb catalyst body K. The N2O concentration at the reactor outlet is low just after the reaction, but gradually increases due to degradation believed to be caused by SO2, and finally reaches the same level as honeycomb catalyst body K.
[0103] In the honeycomb catalyst bodies C and H using the catalyst of the present invention, there is almost no degradation caused by SO2, and even when the NH3 concentration becomes high, it is possible to suppress the NO contained in the exhaust gas. X and N2O, and can convert NH3, NO X And N2O is simultaneously decomposed into H2O and N2, rendering them harmless.
[0104] [Example 15: Honeycomb catalyst body N] (Preparation of First Catalyst Powder (2)) 100 g of amorphous silica powder was added to an aqueous solution of cerium nitrate hexahydrate (Ce(NO3)3·6H2O) and chloroplatinic acid hexahydrate (H2PtCl6·6H2O) and stirred, and then evaporated to dryness on a sand bath. The dried product was calcined at 500°C in air for 2 hours. The calcined product was crushed to obtain a first catalyst powder (2) in which 0.25% by mass of cerium and 0.05% by mass of platinum were supported on the amorphous silica powder.
[0105] 2 parts by mass of the first catalyst powder (2) and 98 parts by mass of the second catalyst powder (1) were added to pure water to obtain a slurry. The slurry was mixed at 140 g / m 2 The coating amount was coated on a honeycomb substrate (the honeycomb substrate had an outer diameter that was in contact with the inner surface of the tube wall of the tubular reactor and the outer surface of the honeycomb catalyst body.) It was dried at 120°C for 2 hours. Then, it was calcined at 500°C for 2 hours to obtain a honeycomb catalyst body N. The amount of platinum contained in the catalyst of the honeycomb catalyst body N was 10 ppm.
[0106] (Evaluation of Catalyst (3)) The honeycomb catalyst body N was embedded and fixed in the tubular reactor. The simulated gas C containing the components shown in Table 3 flowed into the tubular reactor at AV=13Nm / hr (AV=gas volume / geometric surface area of the honeycomb catalyst body), and the temperature of the tubular reactor was set to 359°C, 415°C, 467°C or 500°C. The NH3 concentration and NO X The results are shown in Table 5.
[0107] [Table 3] Table 3
[0108] (Evaluation of Catalyst (4)) The honeycomb catalyst body N is embedded and fixed in the tubular reactor. The simulated gas D containing the components shown in Table 4 is flowed into the tubular reactor at AV=13Nm / hr (AV=gas amount / geometric surface area of the honeycomb catalyst body), and the temperature of the tubular reactor is set to 530°C and left for 50 hours (hydrothermal aging). Afterwards, the simulated gas C containing the components shown in Table 3 is flowed into the tubular reactor at AV=13Nm / hr (AV=gas amount / geometric surface area of the honeycomb catalyst body), and the temperature of the tubular reactor is set to 359°C, 415°C, 467°C or 500°C. The NH3 concentration and NO X The results are shown in Table 5.
[0109] [Table 4] Table 4
[0110] [Example 16: Honeycomb catalyst body O] (Preparation of First Catalyst Powder (3)) 100 g of amorphous silica powder was added to an aqueous solution of cerium nitrate hexahydrate (Ce(NO3)3·6H2O) and chloroplatinic acid hexahydrate (H2PtCl6·6H2O) and stirred, and then evaporated to dryness on a sand bath. The dried product was calcined at 500°C in air for 2 hours. The calcined product was crushed to obtain a first catalyst powder (3) in which 0.5% by mass of cerium and 0.05% by mass of platinum were supported on the amorphous silica powder.
[0111] 2 parts by mass of the first catalyst powder (3) and 98 parts by mass of the second catalyst powder (1) were added to pure water to obtain a slurry. The slurry was mixed at 140 g / m 2 The coating amount was coated on a honeycomb substrate (the honeycomb substrate had an outer diameter that was in contact with the inner surface of the tube wall of the tubular reactor and the outer surface of the honeycomb catalyst body.) It was dried at 120°C for 2 hours. Then, it was calcined at 500°C for 2 hours to obtain a honeycomb catalyst body O. The amount of platinum contained in the catalyst of the honeycomb catalyst body O was 10 ppm. The NH3 concentration and NO X The results are shown in Table 5.
[0112] [Example 17: Honeycomb catalyst body P] (Preparation of First Catalyst Powder (4)) 100 g of amorphous silica powder was added to an aqueous solution of cerium nitrate hexahydrate (Ce(NO3)3·6H2O) and chloroplatinic acid hexahydrate (H2PtCl6·6H2O) and stirred, and then evaporated to dryness on a sand bath. The dried product was calcined at 500°C in air for 2 hours. The calcined product was crushed to obtain a first catalyst powder (4) in which 3% by mass of cerium and 0.05% by mass of platinum were supported on the amorphous silica powder.
[0113] 2 parts by mass of the first catalyst powder (4) and 98 parts by mass of the second catalyst powder (1) were added to pure water to obtain a slurry. The slurry was mixed at 140 g / m 2The coating amount was coated on a honeycomb substrate (the honeycomb substrate had an outer diameter that was in contact with the inner surface of the tube wall of the tubular reactor and the outer surface of the honeycomb catalyst body.) It was dried at 120°C for 2 hours. Then, it was calcined at 500°C for 2 hours to obtain a honeycomb catalyst body P. The amount of platinum contained in the catalyst of the honeycomb catalyst body P was 10ppm. The NH3 concentration and NO X The results are shown in Table 5.
[0114] [Example 18: Honeycomb catalyst body A] For the honeycomb catalyst body A, the NH3 concentration and NO X The results are shown in Table 5.
[0115] [Table 5] Table 5
[0116] As shown in Table 5, compared with the honeycomb catalyst body A, the honeycomb catalyst bodies N and O have a high NH3 decomposition rate in the evaluation (3) and (4) under the conditions of ammonia concentration of 20000ppm and NO concentration of 3000ppm. The honeycomb catalyst body P has a low NH3 decomposition rate in the evaluation (3), so the evaluation (4) was not performed. Therefore, by adding cerium, it is estimated that the durability can be improved, and there is an optimal value for the amount of cerium added.
[0117] [Example 19: Honeycomb catalyst body Q] (Preparation of First Catalyst Powder (5)) 100 g of amorphous silica powder was added to an aqueous solution of cerium nitrate hexahydrate (Ce(NO3)3·6H2O) and chloroplatinic acid hexahydrate (H2PtCl6·6H2O) and stirred, and then evaporated to dryness on a sand bath. The dried product was calcined at 500°C in air for 2 hours. The calcined product was crushed to obtain a first catalyst powder (5) in which 1.25% by mass of cerium and 0.25% by mass of platinum were supported on the amorphous silica powder.
[0118] 2 parts by mass of the first catalyst powder (5) and 98 parts by mass of the second catalyst powder (1) were added to pure water to obtain a slurry. The slurry was stirred at 140 g / m 2 The coating amount was coated on a honeycomb substrate (the honeycomb substrate had an outer diameter that was in contact with the inner surface of the tube wall of the tubular reactor and the outer surface of the honeycomb catalyst body.) It was dried at 120°C for 2 hours. Then, it was calcined at 500°C for 2 hours to obtain a honeycomb catalyst body Q. The amount of platinum contained in the catalyst of the honeycomb catalyst body Q was 50 ppm.
[0119] (Evaluation of Catalyst (5)) The honeycomb catalyst body Q was embedded and fixed in the tubular reactor. The simulated gas E containing the components shown in Table 6 flowed into the tubular reactor at AV=13Nm / hr (AV=gas volume / geometric surface area of the honeycomb catalyst body), and the temperature of the tubular reactor was set to 350℃, 400℃, 450℃ or 500℃. The NH3 concentration and NO X The results are shown in Table 7.
[0120] [Table 6] Table 6
[0121] (Evaluation of Catalyst (6)) The honeycomb catalyst body N is embedded and fixed in the tubular reactor. The simulated gas D containing the components shown in Table 4 is flowed into the tubular reactor at AV=13Nm / hr (AV=gas amount / geometric surface area of the honeycomb catalyst body), and the temperature of the tubular reactor is set to 530°C and left for 70 hours (hydrothermal aging). Afterwards, the simulated gas E containing the components shown in Table 6 is flowed into the tubular reactor at AV=13Nm / hr (AV=gas amount / geometric surface area of the honeycomb catalyst body), and the temperature of the tubular reactor is set to 350°C, 400°C, 450°C or 500°C. The NH3 concentration and NO X The results are shown in Table 7.
[0122] [Example 20: Honeycomb catalyst body R] (Preparation of First Catalyst Powder (6)) 100 g of amorphous silica powder was added to an aqueous solution of cerium nitrate hexahydrate (Ce(NO3)3·6H2O) and chloroplatinic acid hexahydrate (H2PtCl6·6H2O) and stirred, and then evaporated to dryness on a sand bath. The dried product was calcined at 500°C in air for 2 hours. The calcined product was crushed to obtain a first catalyst powder (6) in which 2.5% by mass of cerium and 0.5% by mass of platinum were supported on the amorphous silica powder.
[0123] 2 parts by mass of the first catalyst powder (6) and 98 parts by mass of the second catalyst powder (1) were added to pure water to obtain a slurry. The slurry was mixed at 140 g / m 2The coating amount was coated on a honeycomb substrate (the honeycomb substrate had an outer diameter that was in contact with the inner surface of the tube wall of the tubular reactor and the outer surface of the honeycomb catalyst body.) It was dried at 120°C for 2 hours. Then, it was calcined at 500°C for 2 hours to obtain a honeycomb catalyst body R. The amount of platinum contained in the catalyst of the honeycomb catalyst body R was 100 ppm. The NH3 concentration and NO X The results are shown in Table 7.
[0124] [Example 21: Honeycomb catalyst body S] The amorphous silicon dioxide powder was replaced with titanium dioxide powder (anatase crystal form, specific surface area = 65.8 m 2 / g, 50% particle size = 0.024μm, TiO2 = 97.3%, SO4 = 2.43%, Na2O = 0.003%), except that the honeycomb catalyst body S was obtained in the same way as in Example 15. The amount of platinum contained in the catalyst of the honeycomb catalyst body S was 10ppm. The NH3 concentration and NO X The results are shown in Table 7.
[0125] [Example 22: Honeycomb catalyst body T] The amorphous silicon dioxide powder was replaced with titanium dioxide powder (anatase crystal form, specific surface area = 65.8 m 2 / g, 50% particle size = 0.024μm, TiO2 = 97.3%, SO4 = 2.43%, Na2O = 0.003%), except that the honeycomb catalyst body T was obtained in the same way as in Example 19. The amount of platinum contained in the catalyst of the honeycomb catalyst body T was 50ppm. The NH3 concentration and NO X The results are shown in Table 7.
[0126] [Example 23: Honeycomb catalyst body U] The amorphous silicon dioxide powder was replaced with titanium dioxide powder (anatase crystal form, specific surface area = 65.8 m 2 / g, 50% particle size = 0.024μm, TiO2 = 97.3%, SO4 = 2.43%, Na2O = 0.003%), except that the honeycomb catalyst body U was obtained in the same way as in Example 20. The amount of platinum contained in the catalyst of the honeycomb catalyst body U was 100ppm. The NH3 concentration and NO X The results are shown in Table 7.
[0127] [Example 24: Honeycomb catalyst body N] For the honeycomb catalyst body N, the NH3 concentration and NO X The results are shown in Table 7.
[0128] [Example 25: Honeycomb catalyst body V] A honeycomb catalyst body V was obtained in the same manner as in Example 20 except that the amorphous silica powder was replaced with silica titania powder (composite oxide powder composed of titanium dioxide and silica (main component: titanium dioxide), manufactured by Tronox Limited, GX-550). The amount of platinum contained in the catalyst of the honeycomb catalyst body V was 100 ppm. The NH3 concentration and NO X The results are shown in Table 7.
[0129] [Example 26: Honeycomb catalyst body W] 110 g of cerium (III) nitrate hexahydrate (Ce(NO3)3·6H2O), 385 g of ammonium metatungstate and 55 g of oxalic acid were dissolved in 700 g of water. The aqueous solution was injected into a 300 m2 2 / g or more anatase titanium oxide 715g and specific surface area 90m 2 / g or less anatase-type titanium oxide 385g mixed powder, and kneaded for more than 1 hour. The obtained kneaded product was granulated. The granulated product was dried at 120°C for 4 hours. The dried product was calcined at 500°C in air for 2 hours. The calcined product was crushed to obtain a support containing titanium dioxide (powder containing titanium dioxide, tungsten oxide and cerium oxide).
[0130] The amorphous silica powder was changed to a support containing titanium dioxide (powder containing titanium dioxide, tungsten oxide and cerium oxide). The honeycomb catalyst body W was obtained in the same manner as in Example 20. The amount of platinum contained in the catalyst of the honeycomb catalyst body W was 100 ppm. The NH3 concentration and NO X The results are shown in Table 7.
[0131] [Example 27: Honeycomb catalyst body X] (Preparation of First Catalyst Powder (7)) 100 g of silica-titania powder was added to an aqueous solution of cerium nitrate hexahydrate (Ce(NO3)3·6H2O) and chloroplatinic acid hexahydrate (H2PtCl6·6H2O) and stirred, and then evaporated to dryness on a sand bath. The dried product was calcined at 500°C in air for 2 hours. The calcined product was crushed to obtain a first catalyst powder (7) in which 5.0% by mass of cerium and 1.0% by mass of platinum were supported on amorphous silica-titania powder.
[0132] 2 parts by mass of the first catalyst powder (7) and 98 parts by mass of the second catalyst powder (1) were added to pure water to obtain a slurry. The slurry was stirred at 140 g / m 2 The coating amount was coated on a honeycomb substrate (the honeycomb substrate had an outer diameter that was in contact with the inner surface of the tube wall of the tubular reactor and the outer surface of the honeycomb catalyst body.) It was dried at 120°C for 2 hours. Then, it was calcined at 550°C for 2 hours to obtain a honeycomb catalyst body X. The amount of platinum contained in the catalyst of the honeycomb catalyst body X was 200 ppm. The NH3 concentration and NO X The results are shown in Table 7.
[0133] [Example 28: Honeycomb catalyst body Y] (Preparation of Second Catalyst Powder (2)) A 0.1N sodium hydroxide solution was added to 2000 ml of an aqueous solution containing 9.1 g of iron (II) sulfate heptahydrate (FeSO4·7H2O) to adjust the pH to about 6, and then heated to a temperature of 80°C. 60 g of BEA-type zeolite powder (SiO2 / Al2O3 ratio = 25) was added thereto, and the mixture was stirred at 80°C for 2 hours to obtain a slurry. The slurry was dehydrated using a suction funnel equipped with filter paper (No. 5C). Pure water was poured into the filter cake on the filter paper to wash it. The washed filter cake was dried at 110°C for 12 hours. The dried filter cake was placed in a furnace, heated at 100°C / h, and calcined at 500°C for 5 hours. The calcined product was crushed to obtain a second catalyst powder (2) obtained by ion exchange of Fe ions with zeolite.
[0134] 2 parts by mass of the first catalyst powder (7) and 98 parts by mass of the second catalyst powder (2) were added to pure water to obtain a slurry. The slurry was mixed at 140 g / m 2The coating amount was coated on a honeycomb substrate (the honeycomb substrate had an outer diameter that was in contact with the inner surface of the tube wall of the tubular reactor and the outer surface of the honeycomb catalyst body.) It was dried at 120°C for 2 hours. Then, it was calcined at 500°C for 2 hours to obtain a honeycomb catalyst body Y. The amount of platinum contained in the catalyst of the honeycomb catalyst body Y was 200 ppm. The NH3 concentration and NO X The results are shown in Table 7.
[0135] [Example 29: Honeycomb catalyst body Z] (Preparation of Second Catalyst Powder (3)) 60 g of BEA-type zeolite powder (SiO2 / Al2O3 ratio = 12) synthesized without using an organic structure directing agent (OSDA) was added to 2000 ml of an aqueous solution containing 26.6 g of iron (III) sulfate nonahydrate (Fe(NO3)3·9H2O) heated to 80°C, and then stirred for 2 hours at 80°C to obtain a slurry. The slurry was dehydrated using a suction funnel equipped with filter paper (No.5C). Pure water was injected into the filter cake on the filter paper to wash it. The washed filter cake was dried at 110°C for 12 hours. The dried filter cake was placed in a furnace, heated at 100°C / h, and calcined at 600°C for 5 hours. The calcined product was crushed to obtain a second catalyst powder (3) obtained by ion exchange of Fe ions with zeolite.
[0136] 2 parts by mass of the first catalyst powder (7) and 98 parts by mass of the second catalyst powder (3) were added to pure water to obtain a slurry. The slurry was stirred at 140 g / m 2 The coating amount was coated on the honeycomb substrate (the honeycomb substrate had an outer diameter that was in contact with the inner surface of the tube wall of the tubular reactor and the outer surface of the honeycomb catalyst body.) It was dried at 120°C for 2 hours. Then, it was calcined at 500°C for 2 hours to obtain the honeycomb catalyst body Z. The amount of platinum contained in the catalyst of the honeycomb catalyst body Z was 200ppm. The NH3 concentration and NO X The results are shown in Table 7.
[0137] [Example 30: Honeycomb Catalyst Body AA] (Preparation of First Catalyst Powder (8)) 100 g of silica-titania powder was added to an aqueous solution containing cerium nitrate hexahydrate (Ce(NO3)3·6H2O), chloroplatinic acid hexahydrate (H2PtCl6·6H2O) and iridium nitrate, stirred, and then evaporated to dryness on a sand bath. The dried product was calcined at 500°C in air for 2 hours. The calcined product was crushed to obtain a first catalyst powder (8) in which 2.5% by mass of cerium, 0.5% by mass of platinum and 0.25% by mass of iridium were supported on the silica-titania powder.
[0138] 2 parts by mass of the first catalyst powder (8) and 98 parts by mass of the second catalyst powder (1) were added to pure water to obtain a slurry. The slurry was stirred at 140 g / m 2 The coating amount was coated on the honeycomb substrate (the honeycomb substrate had an outer diameter that was in contact with the inner surface of the tube wall of the tubular reactor and the outer surface of the honeycomb catalyst body.) It was dried at 120°C for 2 hours. Then, it was calcined at 500°C for 2 hours to obtain the honeycomb catalyst body AA. The amount of platinum contained in the catalyst of the honeycomb catalyst body AA was 100 ppm. The NH3 concentration and NO X The results are shown in Table 7.
[0139] [Table 7] Table 7
[0140] As shown in Table 7, when comparing honeycomb catalyst bodies N, Q and R, honeycomb catalyst bodies S, T and U or honeycomb catalyst bodies V and X, the more platinum and cerium are loaded, the higher the NH3 decomposition rate is, the lower the denitration rate is, the higher the outlet N2O concentration is, and the lower the effect of hydrothermal aging on the NH3 decomposition rate is. In addition, compared with honeycomb catalyst bodies N, Q and R using a carrier containing silica, honeycomb catalyst bodies S, T and U using a carrier containing titanium dioxide or honeycomb catalyst body V using a carrier containing silica and titanium dioxide have a slightly lower or roughly the same NH3 decomposition rate in evaluation (5) and evaluation (6), a high denitration rate, and a low outlet N2O concentration. In addition, as shown in Table 7, honeycomb catalyst bodies V and W are roughly the same as honeycomb catalyst body U in evaluation (5) and evaluation (6).
[0141] The honeycomb catalyst body Y obtained by adjusting the pH to about 6 during ion exchange, and the honeycomb catalyst body Z calcined at 600°C using zeolite without OSDA, have a higher denitration rate at 350°C in the evaluation (6) after hydrothermal aging than the denitration rate at 350°C in the evaluation (5) before hydrothermal aging. The denitration rate of the honeycomb catalyst body AA containing iridium is higher than that of the honeycomb catalyst body V.
[0142] As shown in the above results, the catalyst of the present invention can effectively promote the conversion of NH3, NO X NH3, NO in the exhaust gas of N2O X The decomposition reaction of N2O can inhibit the production of NO by-products due to the oxidation reaction of NH3. X It will not be degraded by SO2 that may be contained in the combustion exhaust gas, and it also has excellent high temperature resistance. Explanation of symbols
[0143] A-NH3-containing gas, B-O2-containing gas, C-reaction aid (ammonia or urea), D-cooling air, 2-gas inlet pipe, 3-heat exchanger bypass pipe, 5-mixer, 9-heat exchanger, 10h-heater, 10c, 10c2-cooler, 11, 11a, 11b-reactor, 12, 12a, 12b-catalyst layer, 13-treated gas, 14-measuring instrument (thermometer / concentration meter), 17-control device.
Claims
1. A catalyst for promoting a decomposition reaction of ammonia, comprising a mixture of a first catalyst powder and a second catalyst powder, The first catalyst powder includes a support containing at least one selected from the group consisting of ceria, silica, alumina, titania, zirconia and zeolite, and a noble metal supported on the support. The second catalyst powder includes ion-exchange of at least one ion selected from the group consisting of Fe ions, Ce ions, Co ions, and Cu ions with zeolite.
2. The catalyst according to claim 1, wherein The first catalyst powder comprises a support containing silicon dioxide and / or titanium dioxide and platinum and / or iridium supported on the support. The second catalyst powder includes what is obtained by ion-exchanging Fe ions with BEA-type zeolite.
3. A catalyst for promoting a decomposition reaction of ammonia, comprising a mixture of a first catalyst powder, a second catalyst powder and a third catalyst powder, The first catalyst powder includes a support containing at least one selected from the group consisting of ceria, silica, alumina, titania, zirconia and zeolite, and a noble metal supported on the support. The second catalyst powder includes a substance obtained by ion-exchanging at least one ion selected from the group consisting of Fe ions, Ce ions, Co ions, and Cu ions with zeolite. The third catalyst powder includes titanium oxide, tungsten and / or molybdenum oxide, and cerium and / or vanadium oxide.
4. The catalyst according to claim 3, wherein The first catalyst powder comprises a support containing silicon dioxide and / or titanium dioxide and platinum and / or iridium supported on the support. The second catalyst powder includes a substance obtained by ion-exchanging Fe ions with BEA-type zeolite. The third catalyst powder includes titanium oxide, tungsten oxide, and cerium oxide.
5. A method for rendering a treated gas harmless, comprising the following steps: In the presence of the catalyst according to claim 1, a chemical reaction is carried out to convert NH3 contained in the treated gas into nitrogen and water and to convert NO contained in the treated gas into X The chemical reaction of N2O into nitrogen and water.
6. A method for rendering a treated gas harmless, comprising the following steps: In the presence of the catalyst according to claim 3, a chemical reaction is carried out to convert NH3 contained in the treated gas into nitrogen and water and to convert NO contained in the treated gas into X The chemical reaction of N2O into nitrogen and water.
7. The method according to claim 5 or 6, further comprising the step of adding at least one reaction aid selected from the group consisting of ammonia and urea to the treated gas.
8. The method according to claim 7 further comprises: X and N2O to adjust the amount of the reaction aid added to the treated gas.
9. The method according to claim 5 or 6, further comprising the step of cooling the treated gas.
10. The method according to claim 9, further comprising the step of adjusting the cooling degree of the treated gas according to the temperature of the treated gas.
Citation Information
Patent Citations
Method for removing nitrous oxide in exhaust gas and catalyst for removing the same
JP1996057262A
Catalyst for removing nitrogen oxide and removing method of nitrogen oxide using the same
JP1996257402A
Method and apparatus cleaning ammonia-containing waste water
JP2002066538A
Treating method and apparatus for liquid ammonia remaining in tank
JP2004216300A
Method for manufacturing a catalytic particulate filter and catalytic particulate filter
JP2014508631A